Delayed Latency of Postural Muscles of Individuals with Intellectual Disabilities - J. Walter Tolentino-Castro; J. Walter Tolentino-Castro; Andreas Mühlbeier; Luis Mochizuki; Heiko Wagner; Heiko Wagner (Frontiers in Psychology, 2018)
Individuals with intellectual disabilities (ID) (50 < IQ < 79) show impaired motor and postural control, these impairments are highly related to falls and injuries. Recent studies demonstrated these impairments are related with fine and gross motor development, which are more strongly associated with cognition, and consequently language for individuals with ID than for without ID. Despite these studies, little is known about the structure and functioning of this population's spinal cord, which is highly involved in postural control. The aim of our study was to assess the latency of the reflex responses in postural muscles after unexpected lateral external perturbations, in individuals with intellectual disabilities compared to typically developed participants. We assessed 16 participants with intellectual disabilities, 9 males and 7 females (aged 24.06 ± 8.66 years) and 20 typical developed participants (CG), 11 females, 9 males, (aged 21.20±1.96 years). While the participants were in an upright standing position electromyography was used to collect data from M. obliquus externus abdominis (OE) muscles, which were activated by unpredictable perturbations applied by a servomotor on a hand-held grip, following the lateral external perturbation to the trunk. The intellectual disabilities group presented contralateral OE muscles latency of 85.71±27.24 ms, and CG group presented 68.62±10.25 ms, no differences was found. Ipsilateral OE muscles latency also did not differs between the groups, ID group showed 96.60±30.20 ms and CG group showed 95.57±33.53 ms. Our study furthers the knowledge about the muscular activity of individuals with intellectual disabilities. The present experimental results may suggest unique spinal cord processing of individuals with intellectual disabilities when they are faced with unexpected lateral external perturbations.